Field Performance of Twenty Three Clones of Dalbergia Sissoo in Clonal Seed Orchard - Dogra, A. S.; Nautiyal, S.; Nautiyal, D. P.; Singh, G. (Indian Forester, 2006)
A clonal evaluation trial in clonal seed orchard of twenty-three promising clones of Dalbergia sissoo was established at Pindori Mindo Mind, Hoshiarpur (Punjab) in 1996. The same trial was estimated for the identification of outstanding clones for mass multiplication and field development of this species. The clones from Gonda, UP had overall better performance with an exception of Clone 12 of Pathri, Haridwar, Uttaranchal. Clones from Hanumanghar (Rajasthan) and Yamunanagar (Haryana) performed poorly. The clones 192, 204, 232, and 66 (Gonda, U.P.) and 12 (Pathri, Haridwar, Uttaranchal) were not only high performers but also had better adaptability to this location and therefore, recommended for mass clonal multiplication for future plantation in Punjab. On the basis of growth performance and heritability estimates, height, GBH and clear bole were found to be genetically controlled traits and could be considered reliable for selection for further improvement programmes. It would ensure establishment of healthy and disease resistant vegetative multiplication garden and CSOs with high performers for regular supply of quality planting stock in Dalbergia sissoo.